2018
DOI: 10.1002/icd.2119
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of conflicting information: A touchscreen paradigm to measure young children's selective trust

Abstract: Much recent research has shown that children from age 4 onwards reveal a robust preference for reliable over unreliable informants when choosing whom to trust and learn from. Findings concerning selective model choice in children younger than 4 years have mostly been mixed. The present study developed a new touchscreen‐based paradigm with reduced task demands in order to test 2‐ and 3‐year‐old children (N = 48). Results showed that 3‐year‐olds selectively endorsed information from a previously reliable rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Both these studies engaged participants in a hiding game and two speakers, a reliable and an unreliable one, provided conflicting information regarding the bait's hiding location. This research showed that 3‐year‐olds selectively endorsed the information provided by the more reliable speaker, but 2‐year‐olds did not (Ganea et al., 2011; Hermes et al., 2019). It is important to note, however, that the information the speakers provided in these games was episodic in nature (e.g., where the object had been hidden) rather than semantic (what an object is called).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Both these studies engaged participants in a hiding game and two speakers, a reliable and an unreliable one, provided conflicting information regarding the bait's hiding location. This research showed that 3‐year‐olds selectively endorsed the information provided by the more reliable speaker, but 2‐year‐olds did not (Ganea et al., 2011; Hermes et al., 2019). It is important to note, however, that the information the speakers provided in these games was episodic in nature (e.g., where the object had been hidden) rather than semantic (what an object is called).…”
mentioning
confidence: 92%
“…However, as their selective trust is assessed by testing whom they trust, it is possible to distinguish a distrust in the information from an unreliable speaker from an overall decrease in performance when encountering bizarre circumstances. Hence, the two‐informant design may be considered a clearer test of children's selective trust (see also Hermes et al., 2019 for a discussion of the benefits and performance demands of the standard two informant design).…”
mentioning
confidence: 99%
“…Additionally, when children of this age have the opportunity to evaluate another person's reliability against their own observations, children reduce their trust in that person as an informant (Bridgers et al, 2016;Ronfard & Lane, 2018;Ronfard et al, 2017). Therefore, there is strong and consistent data supporting the view that part of what makes children good learners is that they become active in selecting and weighting social and experiential evidence in acquiring knowledge about the world (Hermes et al, 2018(Hermes et al, , 2019Shafto et al, 2012;Sobel et al, 2010;Sobel & Kushnir, 2013).…”
mentioning
confidence: 99%
“…In addition to the lean and rich interpretation being examined separately, some researchers argue that both lower‐order and higher‐order cognitive abilities may be involved in selective social learning (Hermes et al, 2018; Sobel & Kushnir, 2013). Sobel and Kushnir (2013) developed a theoretical model, which proposes that infants may be using more basic‐level abilities, such as statistical learning, and then progress to using more sophisticated abilities when growing older but only once they have the conceptual background knowledge.…”
mentioning
confidence: 99%
“…Based on previous research, it was expected that infants would be more likely to learn a new word from the reliable speaker rather than from the unreliable one. Although this type of design contrasts with previous research in infancy, it is a more conservative test to measure selective social learning, as infants are presented with two informants and they are then required to choose from whom to learn which can eliminate potential differences between conditions (Hermes, Rakoczy, et al, 2018). Furthermore, a new set of theory of mind tasks were used in the present study to investigate potential correlates.…”
mentioning
confidence: 99%